Dynamics and Pragmatism in the Recruitment of Regional Head Candidates by the “Keadilan Sejahtera” Party (PKS) in the 2020 Pandeglang Regional Election - Iwan Henri Kusnadi; Wawan Wawan; M Dian Hikmawan (Universitas Sultan Ageng Tirtayasa, 2024)
This research seeks to reveal how the recruitment process for regional head candidates is carried out by the “Keadilan Sejahtera” Party (PKS). Especially with the emergence of the incumbent Irna Narulita. A political process that requires the value of pragmatism in nominating regional head candidates is indeed normal, What's more interesting is that this only happens at the local level, namely in Pandeglang Regency, this research uses two theories as its analytical tools, namely the Political Party Recruitment Theory and the Local Bossism Theory. This research was guided by qualitative methods that were operated through an exploratory analysis approach where data was obtained from observations of related sources. The results of this research found that the recruitment of regional head candidates by PKS in the 2020 Pandeglang regional elections showed a biased recruitment process because they did not find candidates who were deemed worthy of being nominated.